Impaired creatinine clearance is a risk factor for cardiovascular outcomes in patients with coronary heart disease and pravastatin reduces events similarly in patients with high and low creatinine clearance levels: results from the LIPID study - West, M (ELSEVIER SCI IRELAND LTD, 2020)
10.1016/S1567-5688(03)91448-6